2006
DOI: 10.15288/jsa.2006.67.754
|View full text |Cite
|
Sign up to set email alerts
|

“I'll Never Drink Like That Again”: Characteristics of Alcohol-Related Incidents and Predictors of Motivation to Change in College Students

Abstract: Objective-Alcohol use and its associated behaviors are among the most common reasons for medical treatment and disciplinary infractions among college students. The purpose of this study was to describe the characteristics of students who had recent serious alcohol-related incidents and to identify predictors of motivation to change alcohol use and heavy drinking in particular, with specific attention to gender. Method-Students (N = 227; 52% female) who had been mandated to attend a session of alcohol education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
111
5
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(135 citation statements)
references
References 39 publications
16
111
5
3
Order By: Relevance
“…Degree of aversiveness to an alcohol-related problem also predicts change in alcohol behaviors (Barnett et al, 2006;Qi et al, 2014); women rate alcohol-related problems as more aversive than men (Qi et al, 2014) and following an alcoholrelated incident may have higher motivation to change drinking behaviors than men. Conversely, male students with HED may not experience alcohol-related problems as aversive and thus may not be interested in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Degree of aversiveness to an alcohol-related problem also predicts change in alcohol behaviors (Barnett et al, 2006;Qi et al, 2014); women rate alcohol-related problems as more aversive than men (Qi et al, 2014) and following an alcoholrelated incident may have higher motivation to change drinking behaviors than men. Conversely, male students with HED may not experience alcohol-related problems as aversive and thus may not be interested in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the valence of consequences (i.e., the positive evaluation of positive consequences and the aversiveness of negative consequences) may be relevant for understanding the natural history of drinking. There is accumulating evidence that aversive experiences are related to subsequent motivation to change (Barnett et al, 2002(Barnett et al, , 2006 and actual behavior change (Merrill et al, 2013), but there is also evidence that negative consequences are not always seen as aversive by drinkers (Mallett et al, 2008(Mallett et al, , 2013Patrick and Maggs, 2011). Research is needed that contributes to our understanding of cognitive and affective processes that precede and follow alcohol-related experiences and how those interpretations are related to subsequent behavior.…”
Section: Future Directionsmentioning
confidence: 99%
“…Approaches that relied on knowledge alone or on brief values clarifi cation alone or with other informational content were consistently ineffective (Larimer and Cronce, 2007). Larimer and Cronce (2007) reported that, of seven studies of interventions with mandated students, fi ve studies showed reduced alcohol use or reduced negative consequences (Barnett et al, 2006;Borsari and Carey, 2005;Fromme and Corbin, 2004;LaChance, 2004;White et al, 2006), whereas two studies showed no reductions in alcohol use (Keillor et al, 2004). Thus, there is emerging support for brief motivational interventions (BMIs) and skills-based interventions with mandated students; however, additional research regarding outcomes of these interventions is warranted, given the limitations of previous studies (e.g., small samples, attrition, and lack of appropriate controls).…”
Section: Interventions With Mandated Studentsmentioning
confidence: 99%